PENERAPAN MODEL PEMBELAJARAN SEARCH, SOLVE, CREATE, AND SHARE (SSCS) UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA - Jusman Jusman (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This research was initiated by learning which was still dominated by teachers without training students to carry out learning activities in the form of problem investigation, problem solving, and decision making; as a result, students' critical thinking skills were less trained. In addition, the test given to the students only measured the level of knowledge and understanding of students so that students' skills were not identified. For this reason, this research sought to improve students' critical thinking skills through search, solve, create, and share (SSCS) learning model. This research was a classroom action research conducted at grade VA students at SDN 021 Sitorajo Kari, totaling 20 students. The instruments were observation sheets and critical thinking skills test. The results showed that the actions taken by the teacher in cycle I reached 65.62% with sufficient category, the student activity reached 62.5% with the sufficient category, and the students' critical thinking skills were were 66.4% with sufficient category. Then, in cycle II, the teacher's action increased to 84.37% with good category, the students’ activity also increased to 81.12% with good category, and the students' critical thinking skills also increased by 76.8% which was in good category. Based on the results of the study, it was concluded that search, solve, create, and share (SSCS) learning model improved the students’ critical thinking skills at grade VA SDN 021 Sitorajo Kari.